2015
DOI: 10.3233/jrs-150694
|View full text |Cite
|
Sign up to set email alerts
|

6-Methyluracil derivatives as acetylcholinesterase inhibitors for treatment of Alzheimer’s disease

Abstract: BACKGROUND:Alzheimer's disease (AD) is the major age-related progressive neurodegenerative disorder. The brain of AD patients suffers from loss of cholinergic neurons and decreased number of synapses [1]. AD is caused by an imbalance between Aβ production and clearance, resulting in increased amount of Aβ in various forms [2]. Reduction of Aβ production and increasing clearance of Aβ pathogenic forms are key targets in the development of potential therapeutic agents for AD treatment. Unfortunately, only nosotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Moreover, Aβ was added to mimic an AD pathological condition because it is involved in protein aggregation and neural toxicity in AD pathogenesis [37][38][39] . tTG and its product isopeptide were detected by Western blot analysis at different molecular weights or by in-cell Western assays.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Aβ was added to mimic an AD pathological condition because it is involved in protein aggregation and neural toxicity in AD pathogenesis [37][38][39] . tTG and its product isopeptide were detected by Western blot analysis at different molecular weights or by in-cell Western assays.…”
Section: Discussionmentioning
confidence: 99%
“…Their experiments revealed that nasal administration of Memogain efficiently transported the drug to the brain with the possibility to inhibit deposition of plaque and enhance behavioral symptoms in AD. Another novel sequence of flavonoid based compound was designed and produced which showed AChEI activity along with advanced glycation end products (AGEs) inhibitory properties and antioxidant potential as well[95].One compound 6-methyluracil derivative was found capable of passing through the blood-brain barrier, enhanced working memory in transgenic mice with amyloid precursor protein/PS1 and considerably decreased the Aβ plaques number and area in the brain[96]. Another compound, β-asarone notably enhanced the learning and memory of APP/PS1 transgenic mice by suppressing Beclin-1-dependent autophagy via the PI3K/Akt/mTOR pathway[97].…”
mentioning
confidence: 99%